Exploring biological heterogeneity and implications on novel treatment paradigm in BRAF-mutant metastatic colorectal cancer. (May 2022) - Rodriquenz, Maria Grazia; Ciardiello, Davide; Latiano, Tiziana Pia; Maiorano, Brigida Anna; Martinelli, Erika; Silvestris, Nicola; Ciardiello, Fortunato; Maiello, Evaristo
Abstract: Approximatively 8–15% of patients with metastatic colorectal cancer (mCRC) harbor mutation in BRAF gene. Recent advances in molecular biology enabled a better knowledge of the molecular heterogeneity within BRAF mutant (BRAF MT ) CRCs, including high rate of overlapping with MSI-H status and detection of non-V600E mutations related to more favorable behavior. Treatment armamentarium has been rapidly growing in this subgroup and includes targeted combinations and immunotherapy for concomitant MSI-H patients, thereby making BRAF MT mCRC an innovative model for precision oncology. Nevertheless, duration of responses to targeted strategies remains unsatisfactory due to the development of secondary resistance, which is currently the field of major clinical research on BRAF MT mCRC. This review explores the molecular, clinical and therapeutic landscape of BRAF MT mCRC as well as an update on current treatment strategies and future perspectives in light of the heterogeneity of BRAF-mutated disease. Furthermore, a novel treatment algorithm for BRAF MT mCRC will be proposed. Highlights: Wide clinical and molecular heterogeneity is seen among patients with BRAF MT mCRC. Encorafenib plus binimetinib combination is superior to chemo in 2nd and 3rd line. Immunotherapy showed encouraging results in concomitant BRAF MT MSI patients. Understanding resistance mechanisms will help to develop new anti-BRAF strategies. New treatment algorithm should consider BRAF molecular profile and clinical features. Novel treatment algorithm will improve outcomes and personalization of the cure.